TEACHING SHORT STORY THROUGH STORYTELLING UNIT IN ACTION FOR EFL LEARNERS - IKA TRISNANTASARI (Fakultas Sastra Universitas Gresik, 2016)
This research was conducted to improving students’ speaking skill through storytelling unit in action for the EFL students in Indonesia. This teaching process provides the package in teaching speaking using pictures in series to be applied in teaching learning process. The research design of this research is descriptive qualitative. The data used in applying the creative strategy in teaching speaking, the procedure in teaching learning process are described in details in this research. This strategy was design for the 7 th graders of junior high school students.